(untitled) (Herald of Journalism, 2025)
The article introduces the digital transformation of modern Kazakhstan, which is developing along an innovative path of development, increasingly developing communication technologies in the period of globalization and digital revolution. Kazakhstani society is moving to a new level of development in the context of digitalization of the information space in the country.The object of the research is the modern media landscape of the 21st century with new digital, network technologies that modernize and influence life in Kazakhstan. The subject of the research is the country’s information infrastructure, which, under the influence of digital transformation, is changing society and the media space, which is largely facilitated by the state program "Digital Kazakhstan".The aim is to study the process of digital transformation in the country against the backdrop of a new technological environment and deepening information globalization, which has not only changed the country’s infrastructure but also influenced lifestyle, media development and perception. To prove it, the following methods were used: principles of historical, complex and systemic analysis, basic concepts of the development of digital transformation of society, generalization of historical, socio-political and information phenomena that are the main factors in the modernization of modern society.The results are as follows: in communication between civilizations, significant results are achieved in the exchange of spiritual and scientific achievements. In the modern world, there is an intensification of information influence, which requires knowledge of the communication specifics of each country, the development of principles of interaction on a national, regional and global scale. Thanks to digitalization, Kazakhstan’s economy should grow by 30%. Currently, Kazakhstan ranks 33rd in the world in terms of digitalization. This program will ensure the development of IT in the country. The introduction of digital technologies is one of the most important tasks, for which 14 projects are being implemented with a total cost of 140 billion tenge. Using new technologies in the country, they plan to increase labor productivity in the industrial sector by one and a half times in five years. In the article, the authors tried to show the transformation of Kazakhstani society, which is following an innovative path of development, implementing the state program "Digital Kazakhstan".